Narrative in Persuasive Communication (by Example of Advertising Discourse) - V. A. Andreyeva (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The article is devoted to the narrative in persuasive communication, which implies an impact on the mental sphere of the addressee, on his / her opinion and assessments in order to encourage him / her to perform certain post-communicative actions in the interests of the addressee. Advertising discourse is considered as a kind of persuasive communication. The author focuses on the narrative as a monotext phenomenon. It is noted that such a narrative is monosubject, and its content is a personal story that allows to implement a strategy of positive evaluation for the presentation of the advertised product. The thesis that the narrative as a trans-text phenomenon in advertising communication is not used, even if we are talking about an advertising campaign, which involves not one, but a series of similar advertising texts, is substantiated. It is shown that in this case the closed discourse formation combines monosubject narrative statements reproducing a single scheme. The author proves that the narrative under the conditions of persuasive communication acquires specific features that vary the narrative pro-type, and the features of generation and structure of the narrative allow it to reveal its persuasive potential in the conditions of advertising discourse.